Temperature influences the development-related phenotypes of Philippine Aedes albopictus: implications for vector control - Edillo, Frances; Ymbong, Rhoniel Ryan; Bolneo, Alyssa Angel; Hernandez, Ric Jacob; Suycano, Mark Windy; Sakuntabhai, Anavaj (The Journal of Infection in Developing Countries, 2026)
Introduction: This study investigated the development-related phenotypes (percent pharate larvae, PPL; hatch rates, HRs; and reproductive outputs, ROs) of Aedes albopictus F1 eggs; with parental eggs collected from selected highland and lowland sites of the major islands in the Philippines (Luzon, Visayas, and Mindanao) in 2018–2020. Methodology: Field-trapped parental Aedes eggs were reared and coupled. Ae. albopictus F1 eggs were separately placed inside environmental chambers (18 °C, 25 °C, and 38 °C) for 6 weeks. PPL, HRs, and ROs were determined. Results: Temperature had significant effects on PPL and ROs of F1 eggs of wet season-collected Ae. albopictus; and on PPL, HRs, and ROs of F1 eggs of dry season-collected samples. Temperature had significant effects on PPL, HRs, and ROs across all sites. No seasonal differences were found for PPL, HRs, and ROs. The means of PPL (14.01%) and HR (10.18%) were the highest at 25 °C and lowest at 38 °C (0.64% and 0.00%, respectively); mean RO (2.5) was highest at 18 °C. Pharate larvae of Ae. albopictus at 38 °C were first reported. PPL, HRs, and ROs were similar between highlands and lowlands in Visayas and Mindanao. Conclusions: Temperature influences the development-related phenotypes of Ae. albopictus. F1 eggs can withstand extreme temperatures, hence are public health threats amidst global warming. Both Ae. albopictus and Ae. aegypti should be included in all-year round vector control strategies against Aedes-borne diseases in the tropics. It is recommended to install water pipelines in the rural mountains to prevent mosquito breeding sites.